Iodine status of pregnant women in a metropolitan city which proved to be an iodine-sufficient area. Is mandatory salt iodisation enough for pregnant women? - YOLDEMİR, AHMET TEVFİK; ANIK İLHAN, GÖKÇE (TAYLOR & FRANCIS LTD, 2016)
The objective of this study was to assess the iodine status of pregnant women in a metropolitan city which was stated as iodine sufficient area after salt iodination program. This multicenter, cross-sectional study was carried out on 3543 pregnant women. Age, gestational weeks, smoking, consumption of iodized salt, dietary salt restriction, history of stillbirth, abortus and congenital malformations were questioned. Spot urine samples were analyzed for urine iodine concentration (UIC). The outcomes were: (a) median UIC in three trimesters of pregnancy and (b) frequency of ID among pregnant women. The median UIC was 73 mu g/L. The median UIC was 77 mu g/L (1-324), 73 mu g/L (1-600) and 70 mu g/L (1-1650) in three trimesters of pregnancy, respectively (p: 0.14). UIC < 50 mu g/L was observed in 36.6% (n: 1295) and UIC < 150 mu g/L was observed in 90.7% (n: 3214) of pregnant women. Only 1% (n: 34) of the pregnant women had UIC levels higher than 500 mu g/L. This study showed that more than 90% of the pregnant women in this iodine-sufficient city are facing some degree of iodine deficiency during their pregnancy. A salt iodization program might be satisfactory for the non-pregnant population, but it seems to be insufficient for the pregnant population.
Keywords: iodine-sufficient; pregnancy; salt iodination; iodine status; Iodine deficiency; THYROID-FUNCTION; URINARY IODINE; DEFICIENCY; CHILDREN; INADEQUATE; NUTRITION; AGE; UK